A cross-cultural exploration of children's perceptions of wellbeing: Understanding protective and risk factors. (March 2020) - Sabolova, Klara; Birdsey, Nicola; Stuart-Hamilton, Ian; Cousins, Alecia L.
Highlights: Welsh and Czech Children identified factors that enhance and inhibit their wellbeing. Disrupted family relations and peer difficulties threaten children's wellbeing. Supportive relationships universally contribute to children's wellbeing. Abstract: There is a growing body of literature on children's wellbeing. However, historically, focus has been on adults' perspectives, leading to adult-centric views of wellbeing. Although recent years have witnessed an increase in researchers eliciting children's perspectives, it is not clear whether children's perceptions of wellbeing are universal, or whether they are culturally distinct. This study sought to explore children's perceptions of wellbeing across Wales and the Czech Republic. Semi-structured interviews were conducted with 53 children aged 9–12 years and analysed via thematic analysis. The results revealed similarities in the perceptions of children in Wales and Czech Republic, with children in both cultures drawing on risk and protective factors that children believe impacts on their wellbeing. Risk factors include disrupted family relationships, peer difficulties, and anxiety, while protective factors include positive parent-child relationships, meaningful friendships, and effective coping strategies. This paper suggests that warm parent-child and child-peer interactions contribute to children's positive socioemotional functioning.